2017
DOI: 10.5301/jva.5000700
|View full text |Cite
|
Sign up to set email alerts
|

Adding access blood flow surveillance reduces thrombosis and improves arteriovenous fistula patency: a randomized controlled trial

Abstract: QA-based surveillance combining Doppler ultrasound and ultrasound dilution reduces the frequency of thrombosis, is cost effective, and improves thrombosis free and secondary patency in autologous AVF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 21 publications
0
33
0
1
Order By: Relevance
“…First, better management and use of existing VA from installation (VA network mapping) to maintenance permitted by use of non-invasive imaging (US-based) including monitoring technologies (online monitoring HD) [149, 153,154] or connected technologies offering 24/7 continuous monitoring of VA patency [155]. The idea behind is to facilitate maturation of newly created AVF and/or to intervene earlier on failing VA to permit percutaneous interventional procedures for restoring patency [156].…”
Section: Va Future Outlookmentioning
confidence: 99%
“…First, better management and use of existing VA from installation (VA network mapping) to maintenance permitted by use of non-invasive imaging (US-based) including monitoring technologies (online monitoring HD) [149, 153,154] or connected technologies offering 24/7 continuous monitoring of VA patency [155]. The idea behind is to facilitate maturation of newly created AVF and/or to intervene earlier on failing VA to permit percutaneous interventional procedures for restoring patency [156].…”
Section: Va Future Outlookmentioning
confidence: 99%
“…It has been found that the size of the anastomotic area and drainage vein are related to the AVF blood flow volume. Blood flow volume is a significant index for evaluating AVF function . After the establishment and maturation of the AVF, the drainage vein gradually becomes arterialized, dilated, and coarsened, thus increasing the blood flow volume.…”
Section: Discussionmentioning
confidence: 99%
“…Blood flow volume is a significant index for evaluating AVF function. 18 After the establishment and maturation of the AVF, the drainage vein gradually becomes arterialized, dilated, and coarsened, thus increasing the blood flow volume. WSS plays an important role in the remodeling process of AVF.…”
Section: Discussionmentioning
confidence: 99%
“…(These are overseas’ references which may not represent that of local Chinese patients.) A recent randomized‐controlled trial showed that intra‐access blood flow‐based surveillance combining Doppler ultrasound and ultrasound dilution reduces the frequency of thrombosis, and improves thrombosis free and secondary patency in AVF …”
Section: Vascular Accessmentioning
confidence: 99%
“…A recent randomized-controlled trial showed that intra-access blood flow-based surveillance combining Doppler ultrasound and ultrasound dilution reduces the frequency of thrombosis, and improves thrombosis free and secondary patency in AVF. 121 For static venous pressure, the intra-access pressure (IAP) is measured using a manometer connected to the dialysis needle prior to turning on the dialysis pump (Table 2). 91,122 A venous segment static pressure ratio >0.5 in grafts or fistulae or an arterial segment static pressure ratio >0.75 in graft is suspicious for significant stenosis.…”
Section: In Graft (D)mentioning
confidence: 99%